Structural mechanics a unified approach - Carpinteri, Alberto (E & FN Spon, 1997)
This book presents a complete and unified treatment of the fundamental themes of structural mechanics, ranging from the traditional to the most advanced topics, covering mechanics of linear elastic solids, theory of beam systems, and phenomena of structural failure. The book considers explicitly all the static and kenetic operators of structural mechanics with their dual character. Topics relating to structural symmetry are covered in a single chapter while dynamics is dealt with at various points. The logical presentation allows the clear introduction of topics such as finite element methods, automatic calculation of framed beam systems, plate and shell theory, theory of plasticity, and fracture mechanics. Numerous worked examples, exercises with complete solutions and illustrations make it accessible both as a text for students and as a reference for research workers and practicing engineers.